MENGANALISIS METODE PEMBELAJARAN BAHASA INDONESIA SERTA MENGENAL METODE PEMBELAJARAN BAHASA INDONESIA DI SDIT ALMA-ADDIN KABUPATEN SUBANG - Intan nur azizah; Yosa Ikhlas Nur Fadilah; Rifia Karlina; Nurfitria (Bajang Institute, 2024)
Learning Indonesian is essentially about teaching students good and correct Indonesian language skills according to its purpose and function. Indonesian language education is one of the important aspects that needs to be taught to students at school. It is not surprising that this subject is given since elementary school, from there students are expected to be able to master, understand and implement language skills. Such as reading, listening, writing and speaking. For this reason, teachers as the spearhead who direct students in achieving educational goals are expected to be able to use innovative media and learning models in Indonesian language learning in the modern era which requires something new, this is because teaching a lesson in a Schools specifically vary depending on the materials, media and methods used. This research aims to describe the problems of Indonesian language education, especially studying how students learn language in Indonesian language learning. The approach used in this research is descriptive qualitative. Primary data was obtained through interview studies of teachers and student guardians. The data collection techniques are observation and interviews